Heat Waves Change Plant Carbon Allocation Among Primary and Secondary Metabolism Altering CO2 Assimilation, Respiration, and VOC Emissions - Werner, Christiane; Fasbender, Lukas; Romek, Katarzyna M.; Yáñez-Serrano, Ana Maria; Kreuzwieser, Jürgen (Frontiers in Plant Science, 2020)
Processes controlling plant carbon allocation among primary and secondary metabolism, i.e. carbon assimilation, respiration, and VOC synthesis are still poorly constrained, particularly regarding their response to stress. To investigate these processes we simulated a 10-day 38°C heat wave, analysing real-time carbon allocation into primary and secondary metabolism in the Mediterranean shrub Halimium halimifolium L. We traced position-specific 13 C-labelled pyruvate into daytime VOC and CO2 emissions and during light-dark transition. Net CO2 assimilation strongly declined under heat, due to three-fold higher respiration rates.Interestingly, day respiration also increased two-fold. Decarboxylation of the C1-atom of pyruvate was the main process driving daytime CO2 release, whereas the C2-moiety was not decarboxylated in the TCA cycle. Heat induced high emissions of methanol, methyl acetate, acetaldehyde as well as mono-and sesquiterpenes, particularly during the first two days. After 10-days of heat a substantial proportion of 13 C-labelled pyruvate was allocated into de novo synthesis of VOCs. Thus, during extreme heat waves high respiratory losses and reduced assimilation can shift plants into a negative carbon balance. Still, plants enhanced their investment into de novo VOC synthesis despite associated metabolic CO2 losses. We conclude that heat stress re-directed the proportional flux of key metabolites into pathways of VOC biosynthesis most likely at the expense of reactions of plant primary metabolism, which might highlight their importance for stress protection.